The increasing prevalence of Enterobacteriaceae as pathogens of diabetic foot osteomyelitis: A multicentre European cohort over two decades - Laura Soldevila-Boixader; Oscar Murillo; Felix W.A. Waibel; Madlaina Schöni; Javier Aragón-Sánchez; Karim Gariani; Dan Lebowitz; Bülent Ertuğrul; Benjamin A. Lipsky; Ilker Uçkay (International Journal of Infectious Diseases)
Objectives: To investigate the microbiological trends of community-acquired diabetic foot osteomyelitis (DFO) over the past two decades in specialized academic centres in Switzerland, Spain, and Turkey. Methods: A retrospective analysis of DFO cohorts (2000-2019) from five centres (Geneva, Zurich, Las Palmas, Barcelona, Istanbul) stratified into four periods (P1-P4) to assess microbiological changes. Results: Among 1379 DFO episodes (76% male, median age 67 years; 90% type 2 diabetes, median duration 17 years), gram-positive bacteria were identified in 82%, including Staphylococcus aureus (47%). Methicillin-resistant S. aureus (MRSA) was more prevalent in Barcelona (36%), Las Palmas (24%), and Geneva (29%) than in Zurich (7%). Over time, gram-positive bacteria remained stable or decreased, particularly in Las Palmas (83% to 65%, P = 0.03). The proportion of MRSA decreased in Geneva (39% to 16%) and Las Palmas (37% to 9%), but remained stable in Barcelona. Enterobacteriaceae prevalence increased, notably in Geneva (16% to 39%, P < 0.01) and Las Palmas (27% to 41%, P < 0.01). Among gram-negative pathogens quinolone resistance was 12.5%. Enterobacteriaceae-DFO was associated with ischemic necrosis (OR 1.65), Las Palmas cohort (OR 3.14), and 2016-2019 period (OR 2.68). Conclusions: A significant increase in Enterobacteriaceae-related DFOs was observed from 2016 to 2019, particularly in Mediterranean Europe.